Mengulik Kembali Peran Pustakawan Melalui Program Kelas Literasi (Studi Kasus Open Library Telkom University) - Vlora, Rani Kurnia; Saputra, Riyo (Program Studi Ilmu Perpustakaan dan Informasi Fakultas Adab dan Humaniora UIN Sulthan Thaha Saifuddin Jambi, 2025)
This article aims to find out and see the role of the library through the literacy class service program at Telkom University's Open Library. The research method used in this study is a qualitative descriptive research method, with data collection techniques carried out through observation, observation, and literature study. The type of data collected is subjective which explains in detail the events or phenomena that are or have occurred. The results of this study indicate that the material taught in the literacy class program is to provide special knowledge related to the academic activities of the community and also especially in writing scientific papers. The modules that have been compiled by Telkom University OpenLibrary librarians in this literacy class program include: Information Search Module, Reference Manager Tools Module, and Academic Integrity & Plagiarism Module. It is hoped that through the literacy class program and also the learning provided which cannot be obtained in the classroom is expected to help and provide additional knowledge, especially students in improving their abilities in writing scientific papers.